Efeitos das condições iniciais do solo na estrutura da floresta e no estoque de carbono numa área em restauração - Silva, Camila Morais Ramos (Universidade Federal de São Carlos, 2025)
Deforestation in tropical regions leads to substantial changes in soil organic matter content, affecting the soil microbial community, nutrient cycling, and the degradation of soil structure. Certain human activities, such as dairy cattle milking facilities, can cause an excessive input of organic matter into the soil, which may increase soil nutrient availability through waste runoff. However, there is a lack of information regarding the effect of organic matter input on the structure of a restored forest, particularly after a decade following the implementation of restoration actions. In a deforested riparian forest area in the southeastern region of the São Paulo state, a forest restoration project was initiated in 2013. Part of this area received waste runoff from a nearby milking facility. The organic matter input into the soil, combined with the positioning of the milking facility at one end of the restoration site, resulted in forming a soil fertility gradient across the restored area. This study assessed whether the initial soil conditions observed during restoration implementation influenced forest structure approximately 11 years after restoration. Specifically, we evaluated the effect of initial soil conditions on total tree basal area, tree density, the number of regenerating individuals, stratification and litterfall accumulation, and the carbon stock stored in the aboveground biomass of the restored forest. At the beginning of the restoration process, soil samples were collected at a depth of 0–20 cm from 10 plots distributed across the entire area. Approximately 11 years after seedling planting, we measured the height and diameter of all trees within these plots, which were used to estimate forest structure parameters. Additionally, we collected accumulated litterfall from five subsamples within each plot. Forest structure exhibited spatial variation within the restored area as a function of initial soil conditions. Areas closer to the milking facility developed denser forests with more regenerating individuals, higher basal area and stratification, and greater litterfall accumulation. Conversely, locations farther from the milking facility displayed lower tree density and fewer regenerating individuals, resulting in a less stratified forest with lower litterfall accumulation. Initial soil conditions positively influenced the carbon stock in the aboveground biomass of trees in the restored forest. Our results demonstrate that the amount of organic matter present during initial seedling planting positively influenced the speed of forest structure recovery and carbon sequestration 11 years later. These findings suggest that soil improvement by adding cattle manure in degraded areas with low organic matter content could enhance the efficiency of tropical forest restoration projects.
Effects of initial soil conditions on forest structure and carbon stock in restored forest
Keywords: Floresta ripária; Descarga de resíduos; Fertilidade do solo; Serapilheira; Biomassa acima do solo; Riparian forest; Waste discharge; Soil fertility; Litter; Aboveground biomass; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::FERTILIDADE DO SOLO E ADUBACAO; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA